2000
DOI: 10.2105/ajph.90.12.1866
|View full text |Cite
|
Sign up to set email alerts
|

An international comparison of cancer survival: metropolitan Toronto, Ontario, and Honolulu, Hawaii

Abstract: OBJECTIVES: Comparisons of cancer survival in Canadian and US metropolitan areas have shown consistent Canadian advantages. This study tests a health insurance hypothesis by comparing cancer survival in Toronto, Ontario, and Honolulu, Hawaii. METHODS: Ontario and Hawaii registries provided a total of 9190 and 2895 cancer cases (breast and prostate, 1986-1990, followed until 1996). Socioeconomic data for each person's residence at the time of diagnosis were taken from population censuses. RESULTS: Socioeconomic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(4 citation statements)
references
References 61 publications
0
4
0
Order By: Relevance
“…Wilson, Jargowsky and Bane added much relevant knowledge on high poverty neighborhood measures [10-12], and our research group has done some work to advance understandings of poor neighborhoods, analogous to this study’s middle poverty neighborhoods [2,3]. They seem prevalently represented by not only the poor, but the near poor and working poor as well as lower-middle and middle class people.…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…Wilson, Jargowsky and Bane added much relevant knowledge on high poverty neighborhood measures [10-12], and our research group has done some work to advance understandings of poor neighborhoods, analogous to this study’s middle poverty neighborhoods [2,3]. They seem prevalently represented by not only the poor, but the near poor and working poor as well as lower-middle and middle class people.…”
Section: Discussionmentioning
confidence: 84%
“…The Canadian survival advantage was systematically replicated across diverse low-income Canadian and US contexts through the 1990s [2-8], culminating in a recent study of colon cancer treatment accessibility and survival in Toronto, Ontario, and San Francisco, California that followed its cohorts until 2006 [9]. In the United States, people with colon cancer who lived in low-income areas experienced less thorough lymph node evaluations and were less likely to receive indicated chemotherapies or to survive.…”
Section: Introductionmentioning
confidence: 99%
“…However, it is important to acknowledge that the strength of relations between neighborhood deprivation and clinical outcomes may vary based on geographic area. For example, previous research has cited a Canadian advantage in cancer survival outcomes for patients from economically deprived neighborhoods relative to some US cities and states, even when controlling for cancer stage (Gorey et al, 2000a, 2000b; Gorey et al, 2011). In those cases, the geographic advantage may have to do with differences in insurance coverage, provider availability, and preventive care between the countries, but it is certainly also possible to find these variations within a single country or region of the country for reasons other than those cited.…”
Section: Discussionmentioning
confidence: 99%
“…Studies of cancer care in impoverished places observed large Canadian advantages. 9 - 13 The poorer the places the larger their advantages. 14 , 15 …”
Section: Introductionmentioning
confidence: 99%